A solar-heated Janus sponge with excellent floating stability for efficient cleanup of heavy oil. (October 2020) - Yang, Jin; Xu, Peng; Yao, Yilin; Li, Yong; Shi, Bing; Jia, Xiaohua; Song, Haojie
Abstract: The inefficient cleanup of viscous heavy oil is thought as a worldwide problem because of its poorer fluidity at room temperature. Herein, we make full use of the photothermal performance to harvest solar energy and convert heat into heavy oil, thus reducing significantly oil viscosity and realizing rapid oil remediation. Specially, the polydopamine as photothermal components, titanium dioxide and perfluorodecyltrichlorosilane as superhydrophobic/superoleophilic source are introduced into the melamine-formaldehyde sponge by deposition method. To be applicable in the marine environments with winds and waves, the bottom side of this sponge subjected to UV irradiation is transferrable from superhydrophobicity to superhydrophilicity. The Janus sponge can keep the balance of movement and never overturned under the action of wind force, thereby enabling this sponge to absorb consecutively spilled heavy oil from marine system. With one simulated solar irradiation, the top and bottom of Janus sponge are heated to a suitable temperature of 90.7 and 70.2 °C, respectively. Relied on these advantages, the Janus sponge can effectively reduce the viscosity of spilled heavy oil and enhance its fluidity, which allow for quick heavy oil absorption up to nearly 12 times of own weight. Meanwhile, it can be also compressed for recycled uses. Graphical abstract: Unlabelled Image Highlights: The Janus sponge was successfully synthesized by successive deposition and final UV irradiation. The Janus sponge exhibited five superhydrophobic sides and a superhydrophilic bottom side. This Janus sponge exhibited excellent mechanical property at a strain of 80% and 50 cyclic compression tests. The Janus sponge could keep excellent floating stability for 20 s or more under marine conditions with winds and waves. The Janus sponge could absorb stably viscous heavy oil by photothermal effect, with absorption capacity to 11.2 g/g.